Preliminary Scale of Reference Values for Evaluating Reactive Strength Index-Modified in Male and Female NCAA Division I Athletes - Christopher J. Sole; Timothy J. Suchomel; Michael H. Stone (MDPI AG, 2018)
The purpose of this analysis was to construct a preliminary scale of reference values for reactive strength index-modified (RSImod). Countermovement jump data from 151 National Collegiate Athletic Association (NCAA) Division I collegiate athletes (male n = 76; female n = 75) were analyzed. Using percentiles, scales for both male and female samples were constructed. For further analysis, athletes were separated into four performance groups based on RSImod and comparisons of jump height (JH), and time to takeoff (TTT) were performed. RSImod values ranged from 0.208 to 0.704 and 0.135 to 0.553 in males and females, respectively. Males had greater RSImod (p < 0.001, d = 1.15) and JH (p < 0.001, d = 1.41) as compared to females. No statistically significant difference was observed for TTT between males and females (p = 0.909, d = 0.02). Only JH was found to be statistically different between all performance groups. For TTT no statistical differences were observed when comparing the top two and middle two groups for males and top two, bottom two, and middle two groups for females. Similarities in TTT between sexes and across performance groups suggests JH is a primary factor contributing to differences in RSImod. The results of this analysis provide practitioners with additional insight as well as a scale of reference values for evaluating RSImod scores in collegiate athletes.